Protective immunity induced by DNA vaccine containing TgGRA35, TgGRA42, and TgGRA43 against Toxoplasma gondii infection in Kunming mice - Youbo Shi; Jianbing Li; Weili Yang; Jia Chen; Jia Chen (Frontiers in Cellular and Infection Microbiology, 2023)
BackgroundToxoplasma gondii can cause congenital infection and abortion in humans and warm-blooded animals. T. gondii dense granule proteins, GRA35, GRA42, and GRA43, play a critical role in the establishment of chronic infection. However, their potential to induce protective immunity against T. gondii infection remains unexplored.ObjectiveThis study aimed to test the efficacy of a DNA vaccine encompassing GRA35, GRA42, and GRA43 in inducing protective immunity against the highly virulent T. gondii RH strain (type I) and the brain cyst-forming PRU strain (type II).MethodsThe eukaryotic plasmids pVAX-GRA35, pVAX-GRA42, and pVAX-GRA43 were constructed and formulated into two- or three-gene cocktail DNA vaccines. The indirect immunofluorescence assay (IFA) was used to analyze their expression and immunogenicity. Mice were immunized with a single-gene, two-genes, or multicomponent eukaryotic plasmid, intramuscularly. We assessed antibody levels, cytotoxic T-cell (CTL) responses, cytokines, and lymphocyte surface markers by using flow cytometry. Additionally, mouse survival and cyst numbers in the brain of mice challenged 1 to 2 months postvaccination were determined.ResultsSpecific humoral and cellular immune responses were elicited in mice immunized with single-, two-, or three-gene cocktail DNA vaccine, as indicated by significant increases in serum antibody concentrations of total IgG, IgG2a/IgG1 ratio, cytokine levels (IFN-γ, IL-2, IL-12, IL-4, and IL-10), lymphocyte proliferation, lymphocyte populations (CD4+ and CD8+ T lymphocytes), CTL activities, and survival, as well as decreased brain cysts, in comparison with control mice. Moreover, compared with pVAX-GRA35 + pVAX-GRA42, pVAX-GRA42 + pVAX-GRA43, or pVAX-GRA35 + pVAX-GRA43, multicomponent DNA vaccine with three genes (pVAX-GRA35 + pVAX-GRA42 + pVAX-GRA43) induced the higher humoral and cellular immune responses, including serum antibody concentrations, cytokine levels, lymphocyte proliferation, lymphocyte populations, CTL activities and survival, resulting in prolonged survival time and reduced brain cyst loads. Furthermore, mice immunized with pVAX-GRA35 + pVAX-GRA42, pVAX-GRA42 + pVAX-GRA43, or pVAX-GRA35 + pVAX-GRA43 showed greater Th1 immune responses and protective efficacy than the single-gene-vaccinated groups.ConclusionThese results demonstrate that TgGRA35, TgGRA42, or TgGRA43 are vaccine candidates against T. gondii infection, and the three-gene DNA vaccine cocktail conferred the strongest protection against T. gondii infection.